2012
DOI: 10.1007/s10120-012-0212-z
|View full text |Cite
|
Sign up to set email alerts
|

The initial experience of dual port laparoscopy-assisted total gastrectomy as a reduced port surgery for total gastrectomy

Abstract: Reduced port surgery (RPS), in which fewer ports are used than that in a conventional laparoscopic procedure, is becoming increasingly popular for various surgeries. However, the application of RPS to the field of gastrectomy is still underdeveloped. We started laparoscopy-assisted total gastrectomy through an umbilical port plus another 5 mm port (dual port laparoscopy-assisted total gastrectomy: DP-LATG) as an RPS for laparoscopyassisted total gastrectomy (LATG). A SILS TM port was inserted into an umbilical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…When dissecting lymph nodes along the suprapancreatic arteries, we found that using the left hand was safe and smooth while retracting the pancreas to the dorsal side using the right hand. Successful results using single-port or reduced-port laparoscopic surgery for distal gastrectomies in patients with early gastric cancer have been reported previously [17][18][19]. An experienced and skillful surgeon can perform such complex laparoscopic gastrectomies after gaining sufficient experience of conventional laparoscopic gastrectomies.…”
Section: Discussionmentioning
confidence: 95%
“…When dissecting lymph nodes along the suprapancreatic arteries, we found that using the left hand was safe and smooth while retracting the pancreas to the dorsal side using the right hand. Successful results using single-port or reduced-port laparoscopic surgery for distal gastrectomies in patients with early gastric cancer have been reported previously [17][18][19]. An experienced and skillful surgeon can perform such complex laparoscopic gastrectomies after gaining sufficient experience of conventional laparoscopic gastrectomies.…”
Section: Discussionmentioning
confidence: 95%
“…Although current surgical procedures for LTG have not yet been widely established and standardized, reports have appeared concerning the application of more advanced techniques, such as robotic total gastrectomy [64,65] and reduced-port LTG [66,67]. Robotic gastrectomy has been reported to provide manipulations as reliable as those provided by LTG.…”
Section: Discussionmentioning
confidence: 99%
“…Kunisaki et al 43 and Kawamura et al 44 compared conventional LTG with dual-port LTG (Table 5). Kunisaki et al reported that the operative time was significantly longer with dual-port LTG (319.0 min) than with conventional LTG (259.0 min).…”
Section: Dual-port or Single-port Ltgmentioning
confidence: 99%